(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Precision agriculture is a trending technology that helps in improving the agricultural productivity. This technique combines various technologies like Internet of Things (IoT), remote sensing, information technology and wireless sensor networks (WSN). In this research, we propose a new technique for adaptive water scheduling in precision agriculture based on wireless sensors like moisture and temperature sensors. In the proposed framework, the secure data transfer in the cloud is achieved using blockchain technology. Further, energy efficient data transfer is attained by means of Improved LEACH algorithm. The data from the sensors are acquired using PIC micro controller module. The acquired data are then transmitted to the cloud using Raspberry Pi module. This data is then secured and verified using block chain-based IoT technique. In this way, the blockchain technology plays a pivotal role in sharing the agricultural data in the cloud in a reliable and transparent manner. Further, blockchain technology also provides data security in a decentralized manner. The main drawback in wireless sensor-based precision agricultural system is the limitation of battery power. To overcome this drawback, we have implemented Improved LEACH protocol for achieving energy efficiency. In this protocol, a new threshold limit is introduced to increase the level of energy efficiency. The usage of blockchain and ILEACH protocol helps in achieving an intelligent farming system. The proposed technique helped in achieving an increased throughput of 63%. Further, the data from other sensors like pH sensor and humidity sensor were transmitted to the cloud in real-time. The entire sensor data were available to the farmers using IoT-based smart phone module to enable remote monitoring.